IN THE ANGST OF THE INVISIBLE EXISTENCE: MIRRORING THE EXISTENTIAL DILEMMA USING BODILY METAPHORS IN THE SELECTED POEMS OF JAYANTA MAHAPATRA AND KEKI N DARUWALLA - Padmanabhan, Radhika; Geetha, B.J. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Indian English poetry since the culmination of the colonial phase took a decisive and deliberately marked shift from the slavish imitation of the romantic writers like Keats, Byron, Shelly, and Wordsworth to a more progressive and experimental style with methodical and thematic innovativeness. It was known as post-independence poetry which heralded the arrival of a new way of composing poems with an indigenous ‘Indianness’ essence, sabotaging the strong clutches of its colonizer’s English mother tongue. Some of the greatest contributors include Nissim Ezekiel, Dom Moraes, P. Lal, Adil Jussawalla, A. K. Ramanujan, R. Parthasarathy, Gieve Patel, Arvind Mehrotra, Pritish Nandy, Kamala Das, K. N. Daruwalla, Shiv Kumar, Jayanta Mahapatra, Meena Alexander, Agha Shahid Ali, Vikram Seth, Manohar Shetty, etc. A large section of poetry produced by these avant-garde writers was based on raw human experiences and expressions with overtones of psychoanalysis, existentialism, surrealism, etc. Another major experimentation conducted by the modern Indian poets was the incorporation of symbols and metaphors, which made an allusive reference to the unvoiced pathos of the survival guilt of the modern Indian man. With the emergent uncertainties and disillusionment of the post-independence scenario, themes like an identity crisis, alienation, feminist concerns, Marxism, etc were projected as close allies with the existential concerns of the era. Using Foucault’s discourse of society on ‘subject’ and ‘power’ in the molding of the individual’s self, the present study marks an attempt to demonstrate how the two selected poets Jayanta Mahapatra and Keki N Daruwalla try to reflect their existential concerns and post-colonial ‘angst’ by meticulously employing differently disabled bodily metaphors.